The new verbal trial planned in the bill on procedural efficiency measures of the public justice service and the European standards - Sigüenza López, Julio (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
If the bill for procedural efficiency measurements of the public Justice service is finally approved as it was sent by the Government to the Spanish Parliament («Cortes Generales»), the current configuration of the verbal trial will change substantially, since it will no longer be processed quick and easily, and may be carried out entirely in writing, contrary to what its name suggests.The proposal seems to be inspired by the regulations applied in various European processes. However, it is far from the standards that inspire such regulation of similar lawsuits in Germany, France, Portugal and other countries of the “euro zone”, which, in our opinion, should make our authorities reconsider the convenience and opportunity of said reform.
Keywords: verbal trial; European standards; oral hearing; written process; procedural efficiency